Surface-electromyography: skin and subcutaneous fat tissue attenuate amplitude and frequency parameters - Baars, H.; Jöllenbeck, T.; Humburg,H.; Schröder, J. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to identify the attenuating influence on surface-EMG amplitude (IEMG) and mean power frequency (MPF) by skin and subcutaneous fat tissue. The electrode-muscle-distance (deltaEM) of the left m. biceps brachii is determined by tissue thickness. This was established by ultrasound in 12 females and 15 males six times each during a 43-week period (n=162). IEMG and MPF were measured during isometric maximum voluntary contractions (MVC). deltaEM explained up to 31 % of the variance of EMG-amplitude during MVC, which corresponds to previous studies on submaximum and maximum contractions. MPF variation was explained by deltaEM with up to 16 % and requires further validation. These results are important for the assessment of long-term training studies and neuromuscular fatigue measurements.